Modeling Agricultural Practice Impacts on Surface Water Quality: Case of Northern Aegean Watershed, Turkey - Avcı, B. C.; Kesgin, E.; Atam, M.; Tan, R. I. (Sprınger, 2022)
The Northern Aegean Watershed has 9032 km2 surface area and it is one of the twenty-one major watersheds in Turkey. Excessive use of fertilizers in farming activities undertaken in the Northern Aegean Watershed has led to nitrate and phosphorus level increases in the watershed surface water. The study aims to simulate the surface water quality over twenty years (2010–2030) using the Soil and Water Assessment Tool (SWAT) for the various potential BMP scenarios. Comparison of simulated results based on the developed BMP scenarios with the simulation results of the existing practices were used to review the efectiveness of the BMP on improving surface water quality. The SWAT-CUP process was used for calibration, validation, and sensitivity analysis. The simulation results can be used as a starting point to further the guidelines for the Ministry of Agriculture and Forest for BMP development on watershed-wide agricultural activities.
Keywords: SWAT; Nitrate; BMP; Surface Water Quality; Fertilizer